1979
DOI: 10.1029/ja084ia12p07288
|View full text |Cite
|
Sign up to set email alerts
|

Spacecraft radio scattering observations of the power spectrum of electron density fluctuations in the solar wind

Abstract: Solar wind electron density power spectra in the solar equatorial region are inferred from observations of phase scintillations and spectral broadening made with the Viking, Helios, and Pioneer spacecraft. The heliocentric distance range covered is 2–215 RS, and for some observations close to the sun the spectra extend to fluctuation frequencies as high as 100 Hz. For heliocentric distances ≳20 RS the equivalent spacecraft‐measured one‐dimensional density spectrum Vne is well modeled by a single power law (f−α… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
105
1

Year Published

2006
2006
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 186 publications
(115 citation statements)
references
References 32 publications
9
105
1
Order By: Relevance
“…The observed power spectrum of the solar wind density, which is also consistent with the famous −5/3 slope, has further proven that turbulent processes are a key component shaping the dynamics of astrophysical plasmas (e.g. Woo & Armstrong 1979;Marsch & Tu 1990). In a similar way, the wealth of information contained in the power spectrum extracted from the hot plasma filling galaxy clusters can help us to significantly advance our knowledge of the intracluster medium (ICM) astrophysics.…”
Section: Introductionsupporting
confidence: 48%
“…The observed power spectrum of the solar wind density, which is also consistent with the famous −5/3 slope, has further proven that turbulent processes are a key component shaping the dynamics of astrophysical plasmas (e.g. Woo & Armstrong 1979;Marsch & Tu 1990). In a similar way, the wealth of information contained in the power spectrum extracted from the hot plasma filling galaxy clusters can help us to significantly advance our knowledge of the intracluster medium (ICM) astrophysics.…”
Section: Introductionsupporting
confidence: 48%
“…The density fluctuation of the interplanetary plasma can also be an error source for small solar offset distances of the ray path. Based on the results of solar occultation measurements (Woo and Armstrong, 1979;Imamura et al, 2005), the error is estimated to be ∼3000 cm −3 for the solar offset distance of 0.1 AU, and decreases to ∼300 cm −3 for 0.3 AU, given the typical time scale of traversing the Venus ionosphere of 10 s. It should be noted that these uncertainties vary with time.…”
Section: Link Budget and Error Estimationmentioning
confidence: 99%
“…The temporal variations of the phase and the intensity of the received signal provide information on the spatial spectrum (power law) of density inhomogeneities, the anisotropy of inhomogeneities, the inner turbulence scale, and the bulk velocity of plasma (Pätzold et al, 1996;Imamura et al, 2005;Efimov et al, 2010). Based on the noise level estimation (Section 5.4) and previous occultation results (Woo and Armstrong, 1979), we expect the phase power spectrum will be obtained up to ∼10 Hz for the solar offset distance of 10 solar radii; such a spectrum would enable us to study, for example, the excess power at small scales (100-600 km) observed by the Nozomi radio occultation (Imamura et al, 2005). The minimum solar offset distance of ∼1.5 solar radii will occur on June 25, 2011 in the renewed cruising plan.…”
Section: Objectivesmentioning
confidence: 99%
“…Note that more realistic values of would not produce any significant changes in the analysis, since model calculations of the g-value are insensitive to . The solar wind turbulence is known to be well described by the Kolmogorov spectrum (q=11/3) for all distances except for the vicinity of the Sun (Woo and Armstrong, 1979). Therefore, we assumed q=11/3 in the analysis.…”
Section: Model Fitting Analysis Of Ips Observationsmentioning
confidence: 99%